Peran Investasi dalam Perspektif Islam untuk Mereduksi Pengangguran dan Mewujudkan Visi Strategis ‘Nawacita’ - Kurniawati Kurniawati (Widya Balina, 2018)
It was discovered that FDIs’ contributes in reducing unemployment rate in Indonesia although is of adiminutive percentage compared to the present population. It was also been known that most of peoplehave no or very little knowledge about FDI. It has been therefore advised that, the government shouldencourage more foreign investments so as to increase the government fund and to reduce theunemployment rate in Indonesia and FDI should as well be disseminated to the country. The existingFDIs is one of strategy in Nawacita Vision to accelarate and transform economic country to lessenpoverty and unemployment .